An Analysis of F. Chopin’s Music Language in Terms of Melody, Harmony and Rhythm - ÜNLÜ, Levent; DINÇ, Ayşegül (Studia Universitatis Babes-Bolyai Musica, 2024)
Frédéric Chopin (1810-1849), one of the composers who reflected and created the spirit of the ‘Romantic Period,’ characterized by increased diversity in style, form, and expression, and the expansion of piano literature, crafted the musical texture in his pieces with a highly personal style, incorporating his unique harmony, flexible formal design, original use of expressive tools, and a free performance technique that didn’t adhere to rigid patterns in rhythm and tempo. Chopin’s distinctive style is particularly visible in the forms he chose for piano music. The flexible forms of his time allowed the composer to create a characteristic style by freely utilizing musical materials. Especially, forms like nocturnes, fantaisies-impromptus, and waltzes, which leave an impression of improvisation, small-scale, and rule-free structures, provided a clear space for the composer’s expressive tools. Indeed, it is possible to identify Chopin’s musical language, especially through his small-scale pieces. The purpose of this research is to analyze the melody construction, harmony, and rhythms of Frédéric Chopin (1810-1849), focusing on selected pieces to provide an interpretation of his musical language based on similarities found in these pieces. Samples from Chopin’s literature, including Op. 27 No. 1, Op. 9 No. 2 and No. 20 Nocturnes, Op. 64 No. 2 Waltz, and Op. 66 Fantaisie-Impromptu, were taken for the study. The research employed a case study design within qualitative research methods, and the obtained data was described descriptively. In conclusion, it was found that Chopin’s harmony encompasses a wide range from simple chord progressions to complex chords. He created simple yet bel canto melodies inspired by the ‘Italian Opera’ embellishments and used rhythms that prioritize the clarity of melody rather than a polyrhythmic approach. This study is believed to contribute to listening and playing practices due to its exploration of the musical materials in the Turkish literature related to Chopin.